Pharmacological management of intra-operative miosis during cataract surgery - Savleen Kaur; Kiran Kumari; Parul Chawla Gupta; Jaspreet Sukhija (Indian Journal of Ophthalmology, 2023)
Cataract surgery requires a well-dilated and stable pupil for a good outcome. Unexpected pupillary constriction during surgery increases the risk of complication. This problem is more pronounced in children. There are now pharmacological interventions that help tackle this unforeseen happening. Our review discusses the simple and quick options available to a cataract surgeon when faced with this dilemma. As cataract surgical techniques continue to improvise and get faster, an adequate pupil size is of paramount importance. Various topical and intra-cameral drugs are used in combination to achieve mydriasis. Despite good pre-operative dilation, the pupil can be quite unpredictable during surgery. Intra-operative miosis limits the field of surgery and increases the risk of complications. For example, if the pupil size decreases from 7 mm to 6 mm, this 1 mm change in pupil diameter will lead to a decrease of 10.2 mm2 in the area of surgical field. Making a good capsulorhexis with a small pupil can be a challenge, even for an experienced surgeon. Repeated touching of the iris increases the risk of fibrinous complications. Removal of cataract and the cortical matter becomes increasingly difficult. Intra-ocular lens implantation in the bag also requires adequate dilation. When dealing with challenging cases like lens subluxation, pseudo-exfoliation, and zonular dehiscence, a small pupil further increases the risk and adversely affects the surgical outcome. Hence, achieving and maintaining adequate mydriasis throughout surgery is essential. This review highlights the risk factors for small pupils during surgery and current management strategies.